A nonenzymatic sensor for xanthine based on electrospun carbon nanofibers modified electrode - Tang, X.; Liu, Yang; Hou, H.; You, T. (Elsevier, 2011)
Xanthine (Xa) determination is of considerable importance in clinical analysis and food quality control. Therefore, a sensitive nonenzymatic amperometric sensor for Xa based on carbon nanofibers (CNFs) has been proposed. The CNFs, which were prepared by electrospinning technique and subsequent thermal treatment, were used to modify carbon paste electrode (CNF-CPE) to construct the amperometric sensor device without any oxidation pretreatment. In application to Xa electrochemical determination, the CNF-CPE exhibited high electrocatalytic activity and fast amperometric response. Various experimental parameters, such as pH and applied potential were optimized. Under the optimal conditions, the dynamic linear range of Xa was 0.03–21.19M (R = 0.9992) with the detection limit low to 20nM (S/N= 3). With good selectivity and sensitivity, the present system was successfully applied to estimate the freshness of fish and determine Xa in human urine, which provides potential application in food quality control and clinical analysis.